Rancang Bangun Sistem Informasi Pendaftaran Calon Member Komara Fitness Berbasis Web - Putra, Bagus Raka (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The registration system is still manual through a ledger that is recorded and does not use technology to store data on existing members. In this research method, the authors use descriptive and qualitative methods. And in solving problems, the authors are guided by software engineering to simplify the design process, the authors use the prototype method. The results of this study can make it easier for admins and members to register web-based members using the prototype method with a UML design model supporting design tools, namely use cases, class diagrams, activity diagrams, the programming language used is PHP and MySQL database, there are several the menu on the web is home, articles, events, promos, service, class, record, user, training schedule and about us.